Modulation of miRNAs in Pulmonary Hypertension - Sudhiranjan Gupta; Li Li (International Journal of Hypertension)
MicroRNAs (miRNAs) have emerged as a new class of posttranscriptional regulators of many cardiac and vascular diseases. They are a class of small, noncoding RNAs that contributes crucial roles typically through binding of the 3′-untranslated region of mRNA. A single miRNA may influence several signaling pathways associated with cardiac remodeling by targeting multiple genes. Pulmonary hypertension (PH) is a rare disorder characterized by progressive obliteration of pulmonary (micro) vasculature that results in elevated vascular resistance, leading to right ventricular hypertrophy (RVH) and RV failure. The pathology of PH involves vascular cell remodeling including pulmonary arterial endothelial cell (PAEC) dysfunction and pulmonary arterial smooth muscle cell (PASMC) proliferation. There is no cure for this disease. Thus, novel intervention pathways that govern PH induced RVH may result in new treatment modalities. Current therapies are limited to reverse the vascular remodeling. Recent studies have demonstrated the roles of various miRNAs in the pathogenesis of PH and pulmonary disorders. This review provides an overview of recent discoveries on the role of miRNAs in the pathogenesis of PH and discusses the potential for miRNAs as therapeutic targets and biomarkers of PH at clinical setting.